VD_FINDINFO Décision / 2012 / 1031 vom 12. Juli 2012 - VD Tribunal cantonal (2012)
CLASSEMENT DE LA PROCÉDURE, ACTE D'ORDRE SEXUEL AVEC UN ENFANT | 187 CP, 189 CP, 319 CPP (CH), 393 al. 1 let. a CPP (CH)